Influence of the throwing direction on biomechanics of movement patterns in handball throws - Marcos Gutiérrez-Dávila; Manuel Alejandro Ortega Becerra; Juan Párraga; José Campos; Francisco Javier Rojas-Ruiz (Federación Extremeña de Balonmano; University of Extremadura, 2013)
The purpose of this study was to compare players' intra-individual variability in the movement pattern of four throwing directions, which were realized to one of the corners of the goal, in presence of the goalkeeper in handball. Five players participated at the first division of Spanish Handball. Each thrower completed 35 throws in different directions. 3D video techniques were used to determine the rectangular components of the spacial positions between 5 body markers and the ball. An analysis of variance was used to detect the changes produced by the direction of the throw. An additional analysis of variance was used to measure the temporary differences of the direction of the throw using the positions of the 5 body markers used by the 3 specialist throwers. The data showed that when the throw was directed to the left side, the time for the throw was significally longer, and when the throw was directed to lower zones, the time of release tended to increase even more, because the ball is released higher.